The Challenges and Resilience of Rubber Farming Households in Transitioning to Oil Palm Cultivation - Ridal Riyos Padri; Elvawati Elvawati; Irwan Irwan (Jurnal Mamangan, 2024)
This study aims to describe the challenges and livelihood resilience of rubber farming households in their migration to oil palm cultivation in Jorong Kapalo Koto, Nagari Abai, Sangir Batang Hari Subdistrict, South Solok Regency. The theory used in this research is the Household Livelihood Resilience Theory as proposed by Longstaff. The method employed is a qualitative approach with a descriptive type, which aims to provide a detailed depiction of the issues being studied. Informants were selected through purposive sampling, involving a total of 10 participants. The types of data used in this study consist of primary and secondary data. Data were collected using non-participant observation, in-depth interviews, and document study. Data analysis followed the Miles and Huberman model, which includes several stages: data collection, data reduction, data display, and drawing conclusions. Based on the results of the study, the challenges faced by rubber farming households in transitioning to oil palm cultivation include: (1) Limited land availability, (2) Limited knowledge about oil palm cultivation, (3) Limited financial capital. Meanwhile, the livelihood resilience of rubber farming households in Jorong Kapalo Koto is reflected in their continued engagement in farming despite pressures and shocks, as shown by: (1) The ability to utilize available land, (2) The ability to leverage social networks.